2015
DOI: 10.1371/journal.pone.0130057
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Low Birth Weight in Malawi: Bayesian Geo-Additive Modelling

Abstract: Studies on factors of low birth weight in Malawi have neglected the flexible approach of using smooth functions for some covariates in models. Such flexible approach reveals detailed relationship of covariates with the response. The study aimed at investigating risk factors of low birth weight in Malawi by assuming a flexible approach for continuous covariates and geographical random effect. A Bayesian geo-additive model for birth weight in kilograms and size of the child at birth (less than average or average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 12 publications
4
32
0
4
Order By: Relevance
“…This study found that child birth order, mother weight, mother height, mother education and family wealth are significant predictors of birth weight. The study is in consistent with the findings of the previous study done by, [11]. The positive effect of mother's education on birth weight in this study is in consistent with other studies, [22], [20] which found mother education as an important factor influencing birth weight.…”
Section: Spatial Effectssupporting
confidence: 93%
“…This study found that child birth order, mother weight, mother height, mother education and family wealth are significant predictors of birth weight. The study is in consistent with the findings of the previous study done by, [11]. The positive effect of mother's education on birth weight in this study is in consistent with other studies, [22], [20] which found mother education as an important factor influencing birth weight.…”
Section: Spatial Effectssupporting
confidence: 93%
“…This output on regional variation has corroborated the finding in similar research studies. Recent studies had showed remarkable variations in the incidence of low birth weight with geographical patterns [24,44]. It is been reported that over 20 million global infants, constituting 15.5 per cent of all births, are born with low birth weight, 95.6% of them in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of low birth weight can be attributed to poverty level in developing countries (16.5%), which is more than double the level in developed regions (7%). Half of all low birth weight babies are born in South Central Asia, where more than a quarter (27%) of all infants weights less than 2500 grams are recorded at birth [44]. The Low birth weight levels in sub-Saharan Africa are found to be around 15% and Central and South America was about (10%).…”
Section: Discussionmentioning
confidence: 99%
“…One of the known factors of LBW is pre-term delivery and intrauterine growth retardation [5,6,7,8]. [c5] Other determinants of LBW are smoking [9,10], [c6] low maternal education [11] [c7] younger maternal age [11], [c8] anaemia [12,13] [c9] marital status, slight weight gain during pregnancy [11], [c10] hypertension [12], [c11] genitourinary tract infection in pregnancy, cesarean delivery [13], [c12] child birth order, mothers weight and height [14]. [c13] parity and fewer prenatal consultations [14].…”
mentioning
confidence: 99%
“…[c5] Other determinants of LBW are smoking [9,10], [c6] low maternal education [11] [c7] younger maternal age [11], [c8] anaemia [12,13] [c9] marital status, slight weight gain during pregnancy [11], [c10] hypertension [12], [c11] genitourinary tract infection in pregnancy, cesarean delivery [13], [c12] child birth order, mothers weight and height [14]. [c13] parity and fewer prenatal consultations [14]. [c14] In addition, low income family, demographic and reproductive variables such as history of low birth weight infants [12] [c15] and history of miscarriage have been reported to be associated with low birth weight [15].…”
mentioning
confidence: 99%